Persistent abdominal pain of a middle aged old female– Think of Amoebic Colitis - Niger, Chowdhury Rifat; Zaman, Chowdhury Akram Uz; Chowdhury, Raj; Hossain, Tamzeed; Mahbub, Tania; Khanam, Rawshan Arra (Bangladesh Critical Care Journal, 2019)
Amebic colitis, also known as amebiasis, is a gastrointestinal disorder caused by invasion of the intestine by the protozoan parasite, Entamoeba histolytica. Although primarily a disease found in underdeveloped countries, this condition may exist in patients who have recently travelled these area. Obtaining an accurate history and testing are crucial for correctly diagnosing and treating amebic colitis. Here we are reporting a case of Amoebic Colitis who has presented with severe abdominal pain and diarrhoea. Bangladesh Crit Care J March 2019; 7(1): 58-60